Split‐thickness skin grafting for reconstruction of auricular skin defects: a statistical analysis. (12th January 2018) - Thuile, Tobias; Larcher, Lorenz; Gatscher, Barbara; Schwaiger, Karl; Deluca, Jenny; Fallaha, Amgiad; Tappeiner, Lukas; Puviani, Mario; Eisendle, Klaus
Summary: Background and objectives: Surgical reconstruction following the removal of large malignant auricular lesions is challenging. While many options for defect closure have been described, in the elderly population usually affected flap surgery, long anesthesia times, patient compliance, and anticoagulant therapy pose additional risks. An alternative quick, simple, and effective method of defect closure is therefore highly desirable. The objective of the present study was to assess the aesthetic outcome, healing process, complications, and recurrence rates associated with unmeshed split‐thickness skin grafts (STSGs) used for covering large auricular skin defects following cartilage‐sparing skin cancer removal. Patients and methods: Under local tumescent anesthesia, 32 patients received STSGs for defect closure following the removal of malignant cutaneous neoplasms of the ear. Results: The average defect size was 8.0 cm². In all cases, complete healing of the recipient site occurred within two weeks. There were no major complications. The aesthetic outcome was rated highly by patients as well as by the dermatosurgeon involved and two independent plastic surgeons. Conclusions: STSGs are a valid option for closing large auricular skin defects. Even large cutaneous tumors of the external ear do not necessarily infiltrate the cartilage. Thus, cartilage‐sparing tumor resection with subsequent defect closure using a STSG is an excellent and quick method associated with high patient satisfaction.